Branding Strategy for Tourism Industry Development Talun District, Cirebon Regency - Sudiana Wachyudi; Tia Listiaty (FKIP, Universitas Palangka Raya, 2024)
Branding is essential for tourist attractions and government agencies, one of which is improving the image and reputation of a tourist attraction or institution so that the wider community can know it. There needs to be an appropriate strategy from the Talun District government, which is the authority in tourism development in Talun District, so the author is interested in examining the branding strategy carried out by Talun District in developing the tourism sector as a tourist destination. This research uses a descriptive type of research with a qualitative approach. The Talun District Government of Cirebon Regency plans the construction of the